Factors Affecting the Financial Performance of Village-Owned Enterprises (BUMDes) - Asniyar; Husriah; Wilda fatmala (International Journal of Multidisciplinary Learners, 2024)
The purpose of this study was to identify variables that affect the financial performance of Torungo Jaya Village-Owned Enterprises. This research was conducted at BUMDes Torungo Jaya, Burangasi Rumbia Village. The population in this study were BUMDes financial reports for the 2019-2022 period and all 40 BUMDes Torungo Jaya and Village Government administrators. The sample used in this study was the BUMDes Torungo Jaya balance sheet report for 2019-2022 and 40 people of which 20 BUMDes administrators and 20 Village Government people to fill out the questionnaire. This research uses a descriptive approach using quantitative methodology, using the BUMDes Torungo Jaya Financial Report as secondary data and the results of questionnaires and interviews as the main data. In this study, notes, questionnaires, observations, and interviews were used as data collection methods. The results showed that the average Return on assets got good criteria results because BUMDes Torungo jaya was able to generate a fairly high profit on its total assets, liquidity ratios measured using the current ratio got very good criteria, the assessment of the ratio of debt to assets to solvency produced very good criteria results, hypothesis testing shows that working capital has a significant negative effect on the financial performance of BUMDes Torungo Jaya while accountability and transparency have no effect on the financial performance of BUMDes Torungo Jaya